The impact of a mega-event on city branding: The European Capital of Culture 2010 and the image of Istanbul - Doğan, Evinç; Sirkeci, Ibrahim (Border Crossing, 2013)
This study examines the ways in which the city image of Istanbul is re-created through the mega-events within the context of the European Capital of Culture (ECoC) 2010. Istanbul “took the stage” as one of the three ECoC cities (Essen for the Ruhr in Germany and Pécs in Hungary), where the urban spaces were projected as the theatre décor while residents and visitors became the spectators of the events. Organisers and agents of the ECoC 2010 seemed to rebrand Istanbul as a “world city” rather than a “European capital”. With a series of transnational connotations, this can be considered as part of an attempt to turn Istanbul to a global city. In this study we examine posters used during the ECoC 2010 to see whether this was evident in the promoted images of Istanbul. The research employs a hermeneutic approach in which representations, signs and language are the means of symbolic meaning, which is analysed through qualitative methods for the visual data (Visual Analysis Methods), namely Semiotics and Discourse Analysis. The analysed research material comes from a sample of posters released during the ECoC 2010 to promote 549 events throughout the year. Using stratified random sampling we have drawn 28 posters (5% of the total) reflecting the thematic groups of events in the ECoC 2010. Particular attention is also paid to the reflexivity of the researchers and researchers’ embeddedness to the object of research. The symbolic production and visual representation are therefore investigated firstly through the authoritative and historically constituted discourses in the making of Istanbul image and secondly through the orders of cultural consumption and mediatisation of culture through spectacular events. Hence enforcing a transnationalisation of the image of the city where the image appears to be almost stateless transcending the national boundaries. Findings and methodology used in this study can be useful in understanding similar cases and further research into the processes of city and place branding and image relationships.